101: Meat and Iron-Rich Food Consumption in Healthy Canadian Infants. Issue 6 (1st June 2014) - Borkhoff, CM; Maguire, JL; Birken, CS; Macarthur, R; Carsley, S; Chen, Y; Parkin, PC
Abstract: BACKGROUND: Iron is an essential micronutrient for normal growth and cognitive development in early childhood. After the first six months of life, iron requirements rise rapidly and infants exclusively fed breast milk beyond six months are at risk for developing iron deficiency. In 2005, Health Canada recommended that iron-rich foods be introduced at six months of age, emphasizing that naturally iron-rich foods such as meat or meat alternatives be infant's first complementary foods, rather than iron-fortified infant cereal. In 2012, Health Canada advised that infants be offered iron-rich foods two or more times per day. Little is known about the meat consumption patterns among infants and young children in Canada. OBJECTIVES: To describe the meat consumption patterns in healthy Canadian children and examine the association between meat consumption and sociodemographic factors. DESIGN/METHODS: A cross-sectional study of healthy children, aged six months to five years, seen for routine primary health care between December 2008 and December 2012 was conducted through a practice-based research network. Meat consumption and sociodemographic factors were measured using standardized parent-completed survey instruments. Adjusted logistic regression was used to determine the independent variables associated with meat consumption. RESULTS: A total of 4614 healthy children (median age 25 months) were included. Most children (94%) consumed meat over a three-day period. Adjusted logistic regression analysis identified the odds of eating meat increased by 6.5% (95% CI 4.9 to 8.2) with each additional month of age. Children of African, Caribbean, Indian-Caribbean ethnicity (OR 0.4 [95% CI 0.2 to 0.8]; P=0.007), South Asian ethnicity (OR 0.4 [95% CI 0.2 to 0.7]; P=0.005), Latin American ethnicity (OR=0.4, 95% CI 0.2 to 0.8, P=0.009) and North American Aboriginal or Oceania ethnicity (OR 0.5 [95% CI 0.3 to 0.9]; P=0.03) were less likely to eat meat. Only 71% consumed at least two servings of meat or other iron-rich foods daily as per Health Canada recommendations. Children from lower income families were less likely to eat meat according to Health Canada recommendations (OR 0.6 [95% CI 0.4 to 0.7]; P<0.001). Poultry was the meat most frequently consumed (83% poultry, 65% red meat, 62% eggs, 41% fish and 6% shellfish). CONCLUSIONS: Most infants and young children eat meat, however almost one third do not eat meat according to the Health Canada recommendations. Eating meat or meat alternatives less than two times per day was associated with a lower family income. The association between poor meat consumption and iron deficiency in this cohort is a focus of future investigation.